Introducing multilingualism a social approach - Weber, Jean Jacques; Horner, Kristine (Routledge, 2018)
"Introducing Multilingualism is a comprehensive and user-friendly introduction to the dynamic field of multilingualism. Adopting a compelling social and critical approach and covering important social and educational issues, the authors expertly guide readers through the established theories, leading them to question dominant discourses on subjects such as integration, heritage and language testing. This second edition has been fully revised and updated, featuring new chapters on multilingualism in new media, the workplace and the family."--Provided by publisher.